2009
DOI: 10.3109/s10165-009-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine versus placebo in Behçet’s disease: randomized, double-blind, controlled crossover trial

Abstract: The effect of colchicine was evaluated in a large cohort of Behçet's disease (BD) patients and compared to placebo. In a randomized, double-blind, controlled crossover trial, 169 patients without major organ involvement were selected consecutively. They fulfilled the International Criteria for Behçet's Disease. Patients were randomly assigned to colchicine or placebo. At 4 months, they were swapped over (colchicine to placebo, placebo to colchicine) for another 4 months. The primary outcome was the overall dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 8 publications
0
34
1
Order By: Relevance
“…In the study by Davatchi et al . (CQ10), the overall disease activity index decreased significantly with colchicine, as did erythema nodosum, although that was not an isolated effect. In the other study noted above (CQ10), erythema nodosum and arthralgia were both significantly improved by colchicine .…”
Section: Clinical Questions (Cqs) Concerning Treatment Of Mucocutaneomentioning
confidence: 85%
See 3 more Smart Citations
“…In the study by Davatchi et al . (CQ10), the overall disease activity index decreased significantly with colchicine, as did erythema nodosum, although that was not an isolated effect. In the other study noted above (CQ10), erythema nodosum and arthralgia were both significantly improved by colchicine .…”
Section: Clinical Questions (Cqs) Concerning Treatment Of Mucocutaneomentioning
confidence: 85%
“…In a cross‐over study in 169 patients with Behçet's disease with no lesions in major organs, Davatchi et al . found that oral ulcers improved significantly more with colchicine than with placebo . In contrast, in a controlled study in 84 patients randomized to colchicine (1–2 mg/day) and placebo groups, Yurdakul et al .…”
Section: Clinical Questions (Cqs) Concerning Treatment Of Mucocutaneomentioning
confidence: 92%
See 2 more Smart Citations
“…In a randomized, double blind, crossover trial comprising of 169 BD patients without major organ involvement, Davatchi et al, reported significant improvement with colchicine in the overall disease activity, oral and genital ulcers, papulopustular lesions, and erythema nodosum. [37] Dapsone was used in our patients as an alternative to colchicine with good clinical response but relapse was seen in 2 out of 7 patients. Sharquie et al, [38] in their double-blind, crossover study of 20 patients, reported significant reductions in the number, duration, and frequency of oral ulcers and number of genital ulcers with dapsone.…”
Section: (Present Study)mentioning
confidence: 97%